Force-activated separation devices: a preventive strategy for intravenous line disconnection in canine patients - Ko, Min-Jung; Kim, Mu-Young (Frontiers in Veterinary Science, 2025)
Intravenous catheters are essential for administering medications and fluid therapy; however, complications such as line disconnection can occur, potentially leading to the discontinuation or delay of treatments. A force-activated separation device (FASD) can be installed between line components to help prevent these complications. Since the FASD has rarely been explored in veterinary settings, a survey of clinicians and clinical applications was conducted to evaluate the necessity, effectiveness, and considerations of this device. The survey revealed that approximately half of the respondents reported line disconnections as occurring “sometimes,” with patient-related causes being significantly more frequent than those caused by medical staff. Respondents noted that replacing a disconnected catheter typically required considerable time and at least two staff members. Despite this, over half of the respondents indicated that no preventive measures were in place. In clinical applications using the FASD, the overall disconnection rate across all patients was 44.3%, with the rate increasing with the patient’s body weight. Large dogs exhibited a disconnection rate of 80% (8 of 10), followed by medium dogs at 55.6% (10 of 18), and small dogs at 31% (13 of 42). Similar to the survey findings, patient-related causes were the most common for line disconnection. Improper separations occurred at a rate of 39.7%, most frequently between the device and the extension set. Line disconnection causes complications, requires manpower and time, and incurs costs. Therefore, preventive strategies are crucial from the perspectives of patients, owners, and clinicians. The FASD can be one of the strategies, particularly in large-breed dogs.